Older Adults' Age-Related Communication and Routine Dietary Habits. Issue 12 (14th October 2020) - Bernhold, Quinten S.; Giles, Howard
ABSTRACT: Using the communicative ecology model of successful aging (CEMSA), this study examined whether or not older adults' ways of communicating about a variety of age-related issues (e.g., making age-related excuses for their shortcomings, teasing other people about their age) predict older adults' dietary habits. Participants were classified as engaged, bantering, and disengaged agers based on their own patterns of age-related communication. The probability of being an engaged ager positively predicted fruit consumption and negatively predicted soft drink consumption. The probability of being a bantering ager negatively predicted vegetable consumption. Results suggest the potential to expand the CEMSA's boundary conditions to include routine dietary habits. Future researchers can build on these findings by utilizing additional methods to assess dietary habits and testing whether or not dietary habits mediate the associations between age-related communication and a variety of health problems.